Which expression simplifies to 2/15

2 months ago

Solution 1

Guest #5493487
2 months ago

Step-by-step explanation:

ðŸ“š Related Questions

Question
What is 4y x 2 when y = 2?
Solution 1

16

Step-by-step explanation:

4 x 2 = 8 x 2 = 16

Question
What is the perimeter of square whose diagonal has a length of 18 radical 2 feet?
Solution 1

9514 1404 393

Â  72 feet

Step-by-step explanation:

The diagonal of a square is âˆš2 times the side length, so you have ...

Â  diagonal = sÂ·âˆš2 = 18âˆš2

Dividing by âˆš2 gives ...

Â  s = 18

The perimeter of a square is 4 times the side length, so is ...

Â  P = 4s = 4(18) = 72

The perimeter is 72 feet.

Solution 2

72ft

Step-by-step explanation:

(18) ^2 = 648

648/2=324

Root 324=18

18*4=72

Question
Expression a. The sum of 24 and 12 divided by 2
Solution 1
Solution 2

18

Step-by-step explanation:

The sum of 24 and 12

divided by 2. means

24 + 12 / 2

36/2

=18

Question
Complete your statement. Round to the nearest hundredth if necessary.
Solution 1

?

Step-by-step explanation:

??????

Solution 2
? What is the question
Question
Combine like terms to simplify 4y+ 6x-2y
Solution 1

2y + 6x

Step-by-step explanation:

Question
Which expression is equivalent to 4a+2b+2a? It keeps bugging me.
Solution 1
If it has the same letter thats what youâ€™re going to add

4a and 2a have the same letter
You would add it 4a+2a equals 6a
Since 2b is the only one with the letter b it will show

6a+2b
Sorry for grammar Lol
Question
A right triangle. The length of the hypotenuse is 13 units . The length of one leg is 5 units. The length of the other leg is b units
Solution 1

approximately Â 13

Step-by-step explanation:

Solution 2

Step-by-step explanation:

Hope this helps :)

Question
What do you call the amount of substance a container can hold?
Solution 1
Itâ€™s either volume or matter
Question
Solve for t in terms of u, v, w, and x.
Solution 1

there's no image lol

Step-by-step explanation

Question
Find formula for g(x) if it is known that g(x-3)=2x-6
Solution 1

The required formula of g(x) is 2x.

We have to determine, formula for g(x) if it is known that g(x-3) = 2x-6.

To obtain the formula of g(x) follow all the steps given below.

According to the question,

The formula of g(x),

g(x - 3) = 2x - 6

• Step1; Â To find the expression (x - 3) = y in the g(x - 3)

Â  Â  Â  Â  Â  Then,

Â  Â  Â  Â  Â  Â

• Step2; Taking the common factor 2,

Â  Â  Â  Â  Â  Â

Â  Â  Â  Â  Â  Â Then,

Â  Â  Â  Â  Â  Â

Â  Â  Â  Â  Â

• Step3; Â Replace x by y,

Â  Â  Â  Â Then,

Â  Â  Â  Â g(x) = 2x

Hence, The required formula of g(x) is 2x.

brainly.com/question/20714290

Solution 2

Did you even look at it? g(x)=2x

Step-by-step explanation:

2x-6=2(x-3), or 2(x).

2647929
842281
748681
586256
406852
368373
348603
324927
199835
130075
112100
106146
77164
23213
22589
19607
17108
13966
10987
3389